Simplify by using the Distributive Property and combining of similar terms: 5(x +3) - 4(2x - 1)

Question

Asked 8/10/2013 1:14:16 PM

Updated 279 days ago|10/12/2017 6:42:26 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

5x+15-8x+4

-3x+19

-3x=-19

x=19/3

x=6 1/3

Question

Asked 8/10/2013 1:14:16 PM

Updated 279 days ago|10/12/2017 6:42:26 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Rating

3

5(x + 3) - 4(2x - 1)

= 5x + 15 - 8x + 4

= -3x + 19

= 5x + 15 - 8x + 4

= -3x + 19

Added 279 days ago|10/12/2017 6:42:26 AM

This answer has been confirmed as correct and helpful.

27,094,575

questions answered

There are no comments.